Measuring the Quality of Locally Engineering Projects - Almudhaffar, Mujtaba A.; Hmood, Faisal K. (Basrah Journal for Engineering Sciences, 2009)
Observing the locally engineering projects done nowadays show weak application of quality assurance. In this paper a questioner paper was designed depending on ten proposed points which could be assumed to represent the steps of quality assurance in any engineering project and could be used to measure the quality degree in it. The questioner have two sides, the first measure the importance of the proposed ten points and the second measure the application of these ten points in the locally engineering projects. A weak understanding of quality assurance and contracts doesn’t contain points forced contractors to follow ISO quality conditions, also low efficiency of inspection instruments and team was found. The paper suggest that curricula of all engineering study must include quality assurance subjects. The importance of the proposed points was found to be (78%) while the quality assurance in the locally engineering projects was found to be (37%). Quality in a bridge in Diwaniya city was calculated and found equal (49%).